2013
DOI: 10.1590/s1519-69842013000100013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of castanhão reservoir on nutrient and suspended matter transport during rainy season in the ephemeral Jaguaribe river (CE, Brazil)

Abstract: Measurements of nutrient and suspended matter concentrations and loads entering and leaving the Castanhão reservoir during the rainy season were carried out to assess the influence of this large reservoir on land-sea fluvial transport in the ephemeral Jaguaribe river basin. Spatial variation indicated statistically significant attenuation of concentrations only for total phosphorous and suspended matter across the reservoir. Strong retention of nutrients and suspended matter loads by the reservoir was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…By comparing the N emission from the cage aquaculture during the producing cycle (12 t) and the fluvial flow from the main contributor Jaguaribe River during the same period (733 t per 6 months) (Molisani et al 2013), we observed that the cage farm contributed with 2 % of 7-7.7 N while river loads and upstream nitrogen sources represented most of N to the reservoir. However, river and aquaculture N inflow (745 t) and regulated dam outflow (85 t) budget showed that the reservoir retained 660 t or 88 % N showing the importance of management of both in-lake (cage aquaculture) and land-based (agriculture, urbanization, industry, cattle) activities for the Castanhão reservoir (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By comparing the N emission from the cage aquaculture during the producing cycle (12 t) and the fluvial flow from the main contributor Jaguaribe River during the same period (733 t per 6 months) (Molisani et al 2013), we observed that the cage farm contributed with 2 % of 7-7.7 N while river loads and upstream nitrogen sources represented most of N to the reservoir. However, river and aquaculture N inflow (745 t) and regulated dam outflow (85 t) budget showed that the reservoir retained 660 t or 88 % N showing the importance of management of both in-lake (cage aquaculture) and land-based (agriculture, urbanization, industry, cattle) activities for the Castanhão reservoir (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Data from Guo and Li (2003) indicate that effluents from cage aquaculture may cause negative effects in areas from the cage to a distance of 20 m or more outwards. During the sampling period, the water inflow into the Castanhão reservoir varied from 13 to 131 m 3 /s while the outflow over the dam was artificially controlled between 5 and 11 m 3 /s (Molisani et al 2013). Considering only the inflow and outflow rates and reservoir volume, an oversimplified water residence time on the reservoir was 4000 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural sources include atmospheric deposition and the denudation of soils; whereas major anthropogenic sources are irrigated agriculture, husbandry, fish aquaculture and urban runoff and solid waste disposal. Of those, only aquaculture released nutrient directly to the reservoir water column (Molisani et al 2013, Avelino 2015, Santos et al 2016. The comparison between estimates of the natural and anthropogenic nutrient loads to the watershed of the Castanhão reservoir indicates that anthropogenic sources correspond to almost all emissions of nitrogen and phosphorus to the reservoir (Table I).…”
Section: Nutrient Emissions To the Castanhão Reservoirmentioning
confidence: 99%
“…Previous observation on nutrient balance in the Castanhão reservoir showed a net retention of over 97% of the total fluvial input of N and P within the reservoir resulting in nutrient accumulation mostly in the hypolimnion (Molisani et al, 2013). With decreasing water depth, wind action can break the stability of the water column, thus favoring water column mixing processes and the resuspension of bottom material and the consequent increase in nutrient concentrations.…”
Section: Discussionmentioning
confidence: 96%